Meditation and Masks, Drums and Dramas Experiential and Participatory Exercises in the Comparative Religions Classroom - Barnard, G. William (Teaching theology and religion, 1999)
In an effort to create a context in which my students might have the opportunity to touch, and to be touched by, the richness, texture, and power of different religious worlds, I have experimented throughout the years with a wide variety of experiential and participatory exercises in the classroom. For example, the students and I (at times with the assistance of an invited expert practitioner) have drummed, danced, gone on shamanic journeys, made masks, done tai chi and hatha yoga, performed dhikr, engaged in mythic psychodramas, practiced different styles of meditation, and so on. In this paper, I examine some of the difficulties and rewards of utilizing these techniques within a university setting. I also explore some of the ways in which a willingness to incorporate these types of exercises into the classroom challenges several current academic pedagogical assumptions.